The multidimensional nature of social support and engagement in contributing to adjustment following spousal loss. (2nd June 2020) - Sullivan, Colleen; Infurna, Frank J.
Abstract: Objectives: Spousal loss is a significant life event that can negatively affect multiple facets of mental and physical health. Social support and engagement are generally found to improve adjustment following adversity, but much less is known regarding which facet of social support and engagement is most predictive of adjustment following spousal loss. This study examined changes in mental health and well-being following spousal loss and which facets of social support and engagement are associated with positive adjustment following spousal loss. Method: Latent growth curve modeling was applied to longitudinal data from 265 individuals who became widowed from the Changing Lives of Older Couples Study to examine: (1) adjustment following spousal loss in depressive symptoms, anxiety and well-being and (2) whether different facets of social support and engagement predict positive adjustment. Results: Depressive symptoms increased following spousal loss, whereas anxiety and well-being remained relatively stable before and after spousal loss. Receiving more instrumental support was associated with lower levels of depressive symptoms and anxiety 6-months following spousal loss. Higher levels of emotional support from one's spouse at baseline was associated with more depressive symptoms and anxiety 6-months following spousal loss. Conclusion: Instrumental support received was the most beneficial facet of social support and engagement. The discussion focuses on how these findings fit into the larger literature of the ways through which social support and engagement lead to adjustment following adversity.